2001
DOI: 10.1016/s0735-1097(01)01575-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated vasodilation of the femoral and brachial artery induced by exercise in healthy nonsmoking and smoking men

Abstract: Conduit arteries react with a flow-mediated dilation in response to whole-body exercise. The impairment of this vasodilation observed in smokers was strongly related to a decrease of endothelium-dependent dilation induced by forearm ischemia, indicating that endothelial dysfunction represents the underlying mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
78
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 37 publications
8
78
1
1
Order By: Relevance
“…During recovery following each exercise, an increased blood flow in the working skeletal muscle returns to the resting levels in a manner described as "a single exponential decay". This relationship has been shown in handgrip (Shoemaker et al, 1994;Kagaya and Homma, 1997;Byström et al, 1998;van Beekvelt et al, 2001), knee extension (Sjøgaard et al, 1988;Rådegran, 1997;Osada et al, 1999), plantar flexion (Leyk et al, 1994;Leyk et al, 1999) and for a bicycle exercise (Gaenzer et al, 2001). FBF during recovery after IHE fitted a single exponential curve.…”
Section: Time Constant (Tc)supporting
confidence: 61%
“…During recovery following each exercise, an increased blood flow in the working skeletal muscle returns to the resting levels in a manner described as "a single exponential decay". This relationship has been shown in handgrip (Shoemaker et al, 1994;Kagaya and Homma, 1997;Byström et al, 1998;van Beekvelt et al, 2001), knee extension (Sjøgaard et al, 1988;Rådegran, 1997;Osada et al, 1999), plantar flexion (Leyk et al, 1994;Leyk et al, 1999) and for a bicycle exercise (Gaenzer et al, 2001). FBF during recovery after IHE fitted a single exponential curve.…”
Section: Time Constant (Tc)supporting
confidence: 61%
“…This physiological flow-dependent vasodilator response of conduit arteries is also seen during exercise. For example, Gaenzer et al observed that bicycle exercise leads to vasodilation of the femoral artery, which correlated with brachial artery FMD (27).…”
Section: Physiological Roles Of the Vascular Endotheliummentioning
confidence: 99%
“…Using a vessel wall movement detector, this 3-month study showed that weight loss increased carotid artery distensibility but found no additional benefit from adding an exercise component to the weight loss program. In contrast, improvement in macrovascular endothelium-dependent vasodilation was reported after acute (16) and chronic exercise programs (11,17) that did not include a weight reduction component. One study (11) found that 3 months of physical training enhanced brachial artery FMD in patients with the polymetabolic syndrome, and a second study (17) observed that 12 weeks of aerobic and resistance training improved brachial artery FMD in subjects with type 2 diabetes.…”
mentioning
confidence: 92%